Penerapan Media Pembelajaran Wordwall untuk Meningkatkan Keaktifan Belajar pada Mata Pelajaran IPA Kelas III di SDIT Muhammadiyah 01 Kotapinang - Nurbaya Harahap; Sakban Sakban; Deprizon Deprizon; Wismanto Wismanto; Radhiyatul Fithri; Salman Salman (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2024)
This research is motivated by the low learning activity of students in science subjects because the learning activities carried out are still using the lecture method which is only centered on the teacher, causing learning to tend to be monotonous so that students feel bored, sleepy, and tired during the learning process. This study aims to improve students' learning activity in science subjects in class IV of SDIT Muhammadiyah 01 Kotapinang by implementing wordwall learning media. This research is a classroom action research (CAR). The subjects in this study were 20 students in class III of SDIT Muhammadiyah 01 Kotapinang. While the object of this research is the application of wordwall learning media to improve students' learning activity. This research was conducted in two cycles, each cycle of which was carried out for two meetings. Each cycle consists of four stages, namely planning, implementation, observation, and reflection. The results of the study on the application of wordwall learning media in science subjects for grade III at SDIT Muhammadiyah 01 Kotapinang are that in cycle I, teacher activity was 78.75% in the good category, student activity was 68.75% in the sufficient category and student learning activity was 74.16% in the sufficient category. In cycle II, the results of the application of wordwall learning media increased, teacher activity was 98.75% in the very good category, student activity was 93.75% in the very good category and student learning activity was 93.54% in the very good category. The results of this study indicate that the application of wordwall learning media in science subjects for grade III at SDIT Muhammadiyah 01 Kotapinang can increase student learning activity.